(untitled) (Latakia University Journal -Basic Sciences Series, 2021)
The ministry of Higher education is keen to develop university admission procedures in line with the student’s skills , and to achieve the best inputs to the educational process and improve the graduates’ qualifications to suit the requirements of the labor market . This development occurs by addressing the challenge facing the education sector especially in the current situation in the country and its impact on educational institutions including Tishreen University in many respects including significant changes in the number of students so it was necessary to conduct a study aimed at : 1-Knowing the behavior that the time series represented to number of students accepted and those that represented to number of graduates and the extent of their stationary over time. 2-to find a statistical model to predict the number of students expected to be admitted to Faculty of science for the coming year, as well as the number of graduates from the same college . The study found that the best model for each of the numbers accepted in the Faculty of science and the number graduates using the methodology of the Box-Jenkins is autoregressive model of the first rank ARIMA(1.1.0) . The Syrian crisis has also adversely affected the stability of student numbers over time. Keywords : Box-Jenkins - ARIMA Models – Forecasting – Stability .